Judge Authority To Cancel The Notary Deed As Authentic Evidence - Moh Adib Aristyawan; Akhmad Khisni (Jurnal Akta, 2019)
The purpose of this study were 1) to identify and explain the authority of a judge to cancel the notarial deed as authentic evidence 2) To identify and explain the condition of the cancellation of a notary and legal consequences of the cancellation of an authentic deed. This research method is using empirical juridical approach "empirical juridical approach used to study the legislation. Specifications research used in this study is a descriptive analysis, from this study is expected to obtain a detailed and systematic description of the problem to be studied. Based on data analysis concluded that 1) Judges have authority give an assessment of a notarial deed which was used including eventually issued a verdict "cancel" the notarial deed. The authority of judges in dismissing a notarial deed in a civil case is based on the plaintiff's request wants in the lawsuit. The judge is not authorized to hear and determine a claim outside of what is included or requested by the parties in the suit so the judges to be passive. 2) The cancellation of the notary deed because of the element of achievement or objective requirements of the power of attorney and the deed of sale. As a result of the law is a) Clear and void as a result, legal acts which do not have legal effect from the occurrence of such legal acts. b) Can be canceled: legal act performed does not have the legal effect since the cancellation. c) Degraded strength of proof (UUJN): an authentic act has the strength of evidence that is complete or perfect in the proceedings, but the forces can be degraded / slowdown / downturn into a deed under the hand when in the making violation of the provisions of the requirements under laws apply. d) Subject to administrative sanctions in the form of verbal warning and a written warning light if violations.Keywords: Authority; Deeds; Notary; Authentic evidence